2010
DOI: 10.1086/653025
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Staphylococcus aureus Colonization and Hospital-Acquired Infection in a Medical Intensive Care Unit after Institution of an Active Surveillance and Decolonization Program

Abstract: Objective.To evaluate the effects of an active surveillance program forStaphylococcus aureuslinked to a decolonization protocol on the incidence of healthcare-associated infection and new nasal colonization due toS. aureus.Design.Retrospective quasi-experimental study.Setting.An 18-bed medical intensive care unit at a tertiary care center in Cleveland, Ohio.Methods.From January 1, 2006, through December 31, 2007, all patients in the medical intensive care unit were screened forS. aureusnasal carriage at admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…21 Fraser et al também alcançaram uma redução de 6,38 para 3,32 casos (p = 0,04; RR 0,53; IC95%: 0,28-0,97) por mil dias de internamento ao aplicar rastreio ativo e descolonização numa UCI de 18 camas. 22 Por outro lado, num estudo britânico envolvendo seis hospitais foram levantadas algumas questões relativas à dificuldade de colocar em prática uma estratégia combinada de rastreio ativo e descolonização universal, nomeadamente: dificuldade em rastreio universal (abrangendo somente 88% dos casos) ou no processo de descolonização (atingindo 41% dos casos) devido à mobilidade dos doentes e curta duração dos internamentos, bem como a falta de estrutura física para isolamento dos doentes, deixando dúvidas relativamente ao papel da descolonização na redução do risco no ambiente hospitalar, preferindo frisar a importância das precauções em controlo de infeção. 23 De facto, não basta implementar rastreios ativos se não existirem condições da estrutura física e boas práticas por parte dos profissionais para levar a cabo as precauções básicas e de isolamento.…”
Section: Resultsunclassified
“…21 Fraser et al também alcançaram uma redução de 6,38 para 3,32 casos (p = 0,04; RR 0,53; IC95%: 0,28-0,97) por mil dias de internamento ao aplicar rastreio ativo e descolonização numa UCI de 18 camas. 22 Por outro lado, num estudo britânico envolvendo seis hospitais foram levantadas algumas questões relativas à dificuldade de colocar em prática uma estratégia combinada de rastreio ativo e descolonização universal, nomeadamente: dificuldade em rastreio universal (abrangendo somente 88% dos casos) ou no processo de descolonização (atingindo 41% dos casos) devido à mobilidade dos doentes e curta duração dos internamentos, bem como a falta de estrutura física para isolamento dos doentes, deixando dúvidas relativamente ao papel da descolonização na redução do risco no ambiente hospitalar, preferindo frisar a importância das precauções em controlo de infeção. 23 De facto, não basta implementar rastreios ativos se não existirem condições da estrutura física e boas práticas por parte dos profissionais para levar a cabo as precauções básicas e de isolamento.…”
Section: Resultsunclassified
“…Because there are no standardized guidelines for the control of MRSA colonization and infection in NICUs, we need multivariable approaches that include identifying colonized neonates and placing them on proper contact precautions, cohorting, encouraging proper hand hygiene of healthcare workers, environmental cleaning and the decolonization of colonized neonates [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, our data revealed that more than one-half of infections occurred in patients whose malignancy was in remission, consistent with other studies. 28,29 Numerous studies have shown the benefits of chlorhexidine and other antiseptics at decreasing rates of healthcare-associated infections, [12][13][14]16,30 however, data on the long-term consequences of the use of these agents on the hospital environment are limited. Studies in adult intensive care unit settings have demonstrated that chlorhexidine use is associated with an overall decrease in MRSA transmission but an increase in colonization with qacA/Bpositive isolates.…”
Section: Discussionmentioning
confidence: 99%